INFLUENCE OF FEEDING NORMALIZED TRACE ELEMENTS IN MINERAL AND ORGANIC FORM ON GROWTH, DEVELOPMENT AND METABOLISM OF YOUNG CATTLE - Ye. Yu. Zalyubovskaya (Ветеринария сегодня)
The paper presents results of body weight and basic measurements of black-motley breed calves born at the OOO “Priamurye” dairy complex in the Tambov Rayon, the Amur Oblast in 2017. The animals were selected using the analogous pair method taking into account their age, body weight and health status. Three groups of six-month old animals were formed: one control group and two experimental groups with 10 animals in each. The housing conditions were similar in all the groups. Based on the obtained data on the amount of nutrients consumed and excreted with feces, the digestibility coefficients of crude protein, crude fat, nitrogen-free extracts and crude fiber – animal feeding nutrients used at the farm – were determined. The calves in the control group were fed the basic diet adopted in the farm, the animals in the first experimental group were fed the basic diet with addition of normalized trace elements (iodine, cobalt and selenium) in mineral form, the animals in the second experimental group were given the same trace elements in organic form. The experiment lasted for 180 days. The investigation revealed that the highest body weight and daily average growth values were observed in the second experimental group. Similar results were obtained with regard to increasing nutrient digestibility coefficients. Thus, the positive effect of trace elements in organic form on growth and development of calves was proved.